2021
DOI: 10.5209/psic.74534
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mastectomy on body image and sexuality in women with breast cancer: a systematic review

Abstract: Objective: The study aims to evaluate the impact of mastectomy on body image and sexuality of women with breast cancer, as well as to provide a general understanding of their quality of life. Method: This review followed the PRISMA guidelines. The expression “Mastectomy AND (sexuality OR “body image”)” was searched in Lilacs, Scielo, Pubmed and Scopus databases. Articles published in English, Portuguese and Spanish between 2010 and 2020 were selected. The text analysis was carried out by peers. Results: 69.3% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…These areas are crucial not only due to the high prevalence of psychological distress among cancer patient but also due to the consequences of such disorders on overall health [ 59 ]. In fact, considering breast cancer, a much more widespread, well-known and well-studied type of cancer among women, a large volume of literature is available on quality of life [ 60 ], sexuality [ 61 , 62 ] and partner relationships [ 63 , 64 ]. Furthermore, future studies should investigate the psychological aspects of sexual experience, shame, body image, desire and avoidance of desire as well as considering the sexual orientation of patients and the specific needs related to it that may emerge.…”
Section: Discussionmentioning
confidence: 99%
“…These areas are crucial not only due to the high prevalence of psychological distress among cancer patient but also due to the consequences of such disorders on overall health [ 59 ]. In fact, considering breast cancer, a much more widespread, well-known and well-studied type of cancer among women, a large volume of literature is available on quality of life [ 60 ], sexuality [ 61 , 62 ] and partner relationships [ 63 , 64 ]. Furthermore, future studies should investigate the psychological aspects of sexual experience, shame, body image, desire and avoidance of desire as well as considering the sexual orientation of patients and the specific needs related to it that may emerge.…”
Section: Discussionmentioning
confidence: 99%
“…As noted by the World Health Organization and the World Health Organization Quality of Life Group (WHOQOL, 1995 ), sexual well‐being is part of people's quality of life. Furthermore, it is widely recognised that mastectomy is the surgical procedure with the greatest impact on body image and sexuality and that these effects can be alleviated by immediate reconstruction (Martins et al, 2021 ; van de Grift et al, 2020 ). Therefore, the study of post‐surgical sexuality and breast well‐being is relevant to health care planning, both for professionals and for public health policy (Martins et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is widely recognised that mastectomy is the surgical procedure with the greatest impact on body image and sexuality and that these effects can be alleviated by immediate reconstruction (Martins et al, 2021 ; van de Grift et al, 2020 ). Therefore, the study of post‐surgical sexuality and breast well‐being is relevant to health care planning, both for professionals and for public health policy (Martins et al, 2021 ). However, little attention has been paid to the sexual well‐being of breast cancer survivors (Cruz et al, 2018 ; Salakari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…negative body image can inevitably affect mood of the woman and her interpersonal relationships, lead to social stigmatization, and consequently social isolation. also, body image disturbance following treatment of cancer may be associated with a variety of changes that can have a significant impact on quality of life (Qol) research has shown that the mastectomy has a negative impact on body image and Qol of women and there was a strong positive correlation between body image and Qol (12,13). furthermore, many women describe alopecia (hair loss) as the most frightening disease related, which has often led to a refusal to continue with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%